Pelican in the wilderness: symbolism and allegory in women’s evangelical songs of the Gàidhealtachd - Macleod Hill, Anne Isabell Martin (The University of Edinburgh, 2016)
The Pelican in the Wilderness: Symbolism and allegory in women’s evangelical songs of the Gàidhealtachd The Gaelic women’s song tradition has been studied in depth, and the post- Reformation Church and its impact on the Gàidhealtachd examined from various perspectives, yet the body of evangelical song which shows the interaction of the two is possibly the least explored area of traditional Gaelic verse and the least understood outside the immediate environment in which it was created. In their devotional songs, evangelical elegies and waulking songs, generations of women have left a record of the domestic, spiritual and cultural life of the Gàidhealtachd which would be difficult to retrieve from any other source. The present study provides access to this important literary and cultural resource by creating a research corpus of 600 poems, representing the work of 165 women from many different parts of the Gàidhealtachd, dating from the mid-eighteenth century to the present day. The historical, theological and literary background to the songs is explored, using both a range of secondary sources and the words of selected poets as they articulate and define contemporary events within the context of Reformed doctrine. Analysis across the corpus shows songs creating an allegorical world within which every creature, person and place is imbued with spiritual significance, each acting as a mnemonic for an associated biblical paradigm. This use of scriptural and doctrinal allusion is functional rather than purely ornamental, with core metaphors expressed and made authoritative in lexicons of honorifics, epithets and poetic place names. The thesis facilitates fuller reading of spiritual song by explaining the symbolic significance of the above elements, demonstrating their role in creating contextual settings, linking songs into a network of biblical, doctrinal and poetic texts, extending and validating the poet’s message. The functioning of this referential system is further explored in detailed literary analysis of the work of a representative sample of poets, each of whom is set in her own social and historical context.
Keywords: Gaelic song; women; evangelism; symbolism